Kajian terhadap kepadanan Facebook sebagai teknologi untuk berkongsi maklumat semasa banjir - Siti Hasanah, Ishak (2015)
Social media is gaining its popularity as one of the most used ICT platform for information sharing. Recently, social media has been identified as one of the important communication platforms to disseminate information during the event of disaster. Although it has been acknowledged as one of the most useful platforms to disseminate information, there are situations where this platform has been found notsuitable to support this task. Thus, examining the fit between the task and technology can enhance the efficiency of information sharing. The main aim of this study is to identify the factors that influenced task technology fit using social mediaespecially Facebook when sharing information during the flood. Theory of task-technology fit (TTF) has been used as an underlying theory for this study. This study administered web based questionnaire as the data collection technique to obtain data from respondent which is the user of National Security Counsil’s Facebook. Then, the obtained data is analyzed using partial least square (PLS) technique. SmartPLS 2.0 software was used to validate the research model and test the proposed research hypotheses.The findings showed that task characteristic has a strong influenced over technology characteristic to determine the fit between information sharing task and Facebook technology. Theoretically, this study developed a better understanding of what influence task technology fit using Facebook to share information during the event of flood; examined the significant factors that contribute to higher task technology fit during the flood; and proposed a theoretical model that can be used to predict the fit between information sharing task and Facebook during the occurance of flood. Practically, this study contributes by proposing a mechanism to the government agencies on how to improve the fit between Facebook and information sharing task duringflood.